2005
DOI: 10.1093/rheumatology/kei163
|View full text |Cite
|
Sign up to set email alerts
|

The effect of foot orthoses in rheumatoid arthritis

Abstract: Foot orthoses were effective as an adjuvant in the management of rheumatoid foot. They significantly reduced pain, disability and activity limitation, as measured by the FFI, with minor adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 15 publications
2
18
0
5
Order By: Relevance
“…I dati emersi da questo lavoro confermano l'opportunità dell'impiego, oltre ad adeguata terapia farmacologica, di una attenta valutazione clinica del piede reumatoideo anche in una fase precoce di malattia, che possa consentire di adottare rapidamente eventuali supporti meccanici, quali ortesi plantari, come ausilio nella prevenzione delle alterazioni anatomiche che si possono instaurare (19). Nonostante l'efficacia di supporti meccanici sia stata dimostrata sia in lavori di revisione (20,21) che in uno studio longitudinale di 6 mesi che ha evidenziato una riduzione, già entro il primo mese dall'applicazione della ortesi, del dolore e della limitazione funzionale (22), al momento non vi sono specifiche linee guida per la prescrizione della tipologia di ortesi plantare per i soggetti affetti da AR. La prescrizione spesso si basa su modelli standardizzati che non considerano il tipo specifico di alterazione strutturale presentata dal singolo soggetto e non ci si orienta sull'utilizzo di calzature idonee ed individualizzate in base alla tipologia dell'alterazione del piede (23)(24)(25).…”
Section: Discussioneunclassified
“…I dati emersi da questo lavoro confermano l'opportunità dell'impiego, oltre ad adeguata terapia farmacologica, di una attenta valutazione clinica del piede reumatoideo anche in una fase precoce di malattia, che possa consentire di adottare rapidamente eventuali supporti meccanici, quali ortesi plantari, come ausilio nella prevenzione delle alterazioni anatomiche che si possono instaurare (19). Nonostante l'efficacia di supporti meccanici sia stata dimostrata sia in lavori di revisione (20,21) che in uno studio longitudinale di 6 mesi che ha evidenziato una riduzione, già entro il primo mese dall'applicazione della ortesi, del dolore e della limitazione funzionale (22), al momento non vi sono specifiche linee guida per la prescrizione della tipologia di ortesi plantare per i soggetti affetti da AR. La prescrizione spesso si basa su modelli standardizzati che non considerano il tipo specifico di alterazione strutturale presentata dal singolo soggetto e non ci si orienta sull'utilizzo di calzature idonee ed individualizzate in base alla tipologia dell'alterazione del piede (23)(24)(25).…”
Section: Discussioneunclassified
“…The results of this RCT agreed with the meta-analysis in that foot orthoses did not increase foot function. Additionally, 2 observational studies investigated foot function (27,34). These studies used the FFI and the FFI disability subscale, respectively, as their outcome measures.…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…Non-pharmacological interventions for RA that include foot orthoses and footwear can reduce pain and disability and improve long-term outcomes with existing and potential foot problems [8]. Previous studies have reported on the clinical effectiveness of foot orthoses in people with established RA, ranging from simple insoles to customised foot orthoses [9][10][11][12]. Clark [13] reported that few studies have undertaken a cost effectiveness analysis to investigate the cost implication of the prescription of foot orthoses for people with established RA, despite the high prevalence of foot involvement and the high direct cost of RA related health care to the UK economy.…”
Section: Introductionmentioning
confidence: 99%